Philippines : 2019 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2020)
This 2019 Article IV Consultation with Philippines highlights that the economic performance remains strong. The discussions focused on macroeconomic policies to keep the economy close to balance under the baseline outlook and risk scenarios; strategies for macroprudential policies to address risks from a potential renewed acceleration in credit growth; and policies and reforms to foster stronger and inclusive growth. Growth regained momentum in the second half of 2019 following a slowdown in the first half. The latter primarily reflected budgetary developments, with some temporary government underspending in the early part of the year. A decisive monetary policy tightening in response to the inflation spike and overheating risks in 2018 and weaker external demand also contributed. The structural reform momentum and infrastructure push remain strong. Gross domestic product growth is projected to rise further in the near term, underpinned by government spending acceleration and the recent monetary policy easing. Risks to the outlook are to the downside, reflecting risks to the global economy from increased trade tensions, shifts in global financial conditions, and natural disasters.